Complexation Starch with Alkylated Urea as Controlled Release Fertilizer - Akbar Pramuditya, Muhammad
Urea is one of the most used fertilizer in agriculture sector due to its nitrogen content of 45- 57%. However, only about 20-30% nitrogen can be absorbed by plant. The remaining nitrogen which is not be absorbed by plant can pollute the environment especially soil water. Additionally, urea is easy to decompose and may pollute the environment due to leaching and being carried away by rain . Tn this research, urea was modified by alkylation with subsequent complexation with starch. Starch is used as it is a natural polymer with large abundance in nature and biodegradable. Starch has two components which are amylose and amylopectin. Amylose can form a left handed single helix having a hydrophobic canal. Therefore, the hydrophilic urea needs to be modified to increase its hydrophobic by reacting it with alkyl bromide. An Inclusion complex will be formed because of hydrophobic interactions between alkylated urea and amylose canal. The complexation is expected to result in fertilizer which releases its nutrient in a controlled manner, known as controlled release fertilizer. In this research, starch was isolated from cassava with a yield of 16% and amylose content of 57,11%. FTIR of the isolated starch showed a peak in the wavenumber 3300-3500 cm- 1 which corresponded to -OH groups. Alkylated urea was synthesized by reacting urea and 1- bromodecane at a temperature 60-70 °C for 50 minutes to result in N-decylurea. FTIR of the product showed an -NH peak at a wavenumber of around 3300-3400 cm- 1 • Moreover, there was C=O peak at wavenumber of around 1600-1700 cm- 1 • Starch-N-decylurea inclusion complex was formed by mixing starch and N-decylurea at a temperature of around 82-90 °C for 120 minutes. FTIR result showed that inclusion complex had a similar spectrum to starch having an -OH peak at wavenumber of around 3300-3500 cm-1 • This shows that N-decylurea was complexed inside the amylose canal. The XRD results showed that there were peaks at 28 of 12.84° and 19.82 o was for the complex I 0%, 12.88 o and 19.86 o for the complex 30%, and 12.98° and 19.88° for the complex 50%. The SEM results showed that starch-N-decylurea inclusion complex had different morphology compared to starch, urea, as well as N-decylurea. Starch had a granular morphology, urea had a cubic morphology, N-decylurea had a block morphology, while starch-N-decylurea inclusion complex had tubular and block morphology. The study of nitrogen release showed an order from the slowest to the fastest which was N decylurea< complex 50%< complex 30% <complex I 0% <urea. This indicates that the starch N-decylurea inclusion complex had a slower rate of nitogen release compared to urea and the starch-N-decylurea inclusion complex had a faster rate of nitrogen release than N-decylurea. This indicates that starch played an important role in the nitrogen release. Starch likely affected the rate of the nitrogen release in soil by becoming food source for bacteria or microbes in soil.